2006
DOI: 10.1016/j.eurpsy.2006.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Quetiapine in relapse prevention in alcoholics suffering from craving and affective symptoms: a case series

Abstract: Although uncontrolled case observations can only be interpreted with caution quetiapine seems to deserve further investigation and may hold the potential for preventing alcohol relapse in alcoholics suffering from additional above-mentioned symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 26 publications
1
20
0
1
Order By: Relevance
“…These findings extend the clinical literature suggesting that quetiapine may be effective for the treatment of alcohol dependence. These results are consistent with previous reports of quetiapineinduced blunting of alcohol craving, both in open-label studies (Croissant et al 2006;Martinotti et al 2008;Sattar et al 2004) and in a placebo-controlled trial (Kampman et al 2007). While the results for alcohol craving are clearly supportive of the potential clinical utility of quetiapine for alcoholism treatment, the findings for subjective intoxication and sedation lend themselves to alternative explanations.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings extend the clinical literature suggesting that quetiapine may be effective for the treatment of alcohol dependence. These results are consistent with previous reports of quetiapineinduced blunting of alcohol craving, both in open-label studies (Croissant et al 2006;Martinotti et al 2008;Sattar et al 2004) and in a placebo-controlled trial (Kampman et al 2007). While the results for alcohol craving are clearly supportive of the potential clinical utility of quetiapine for alcoholism treatment, the findings for subjective intoxication and sedation lend themselves to alternative explanations.…”
Section: Discussionsupporting
confidence: 92%
“…An additional chart review of nine patients admitted to a residential rehabilitation program suggested that quetiapine was well tolerated and associated with significant decreases in anxiety, improvements in sleep, and lower craving for alcohol (Sattar et al 2004). Published single-case (Lindberg et al 2006) and observational studies (Croissant et al 2006) suggested that quetiapine was well tolerated and may be effective in treating alcoholism. An open-label study of quetiapine in patients with comorbid schizophrenia-spectrum and substance use disorders suggested that the severity of substance abuse decreased over the course of a 12-week trial of quetiapine, as indicated by reduced number of substance use days and money spent on alcohol/drugs (Potvin et al 2006).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Obwohl in der Mehrzahl der durchgeführten Studien keine positiven E ekte belegt werden konnten, fanden sich in einigen Fallserien Hinweise auf Anticravingeigenscha en des atypischen Antipsychotikums Quetiapin [55,56].…”
Section: Weitere Ansätzeunclassified
“…Another atypical antipsychotic drug, quetiapine, has been evaluated in a case study [160] and an open-label study [161] in patients with alcohol dependence and comorbid psychiatric diagnosis. Both studies demonstrated that quetiapine was well tolerated and in the latter study, the medication not only reduced alcohol consumption and overall psychiatric symptom intensity but also significantly reduced craving.…”
Section: Clinical Evidence For the Use Of Atypical Dopamine D2 Antagomentioning
confidence: 99%